Analysis of repeat LSCS in a tertiary care centre - Poovathi, M.; T. S., Suilharsini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Caesarean section (CS) rates continue to increase worldwide, particularly in middle and high-income countries without evidence indicating substantial maternal and perinatal benefits from the increase and some studies showing negative consequences for maternal and neonatal health. The objective of this study is to analyse the repeat caesarean section rates in a tertiary centre. Methods: This is a retrospective study carried out in the Department of Obstetrics and Gynaecology, Pudhukottai Medical College, Tamil Nadu, India for a 12-month period from January 2017 to December 2017 with the aim to analyse the rate and indications for caesarean section and to identify the measures to decrease its incidence if possible. A total of 2654 cesarean deliveries were conducted in one year, out of which 1380 (51.99%) were primary cesarean sections and 1274(48%) were repeat cesarean sections. Results: Repeat LSCS is more common in age group of 21-30 years (80%) and in second gravida (90.42%). The incidence of caesarean section is 94.6%. Patients who had successful trial of scar were 73. In all these patients, measures were taken to shorten the 2nd stage of labour either by giving episiotomy alone or by application of outlet forceps or vacuum. Out of these 62 (84.9%) patients were delivered by episiotomy alone. Conclusions: Caesarean section has become one of the commonly performed surgeries in obstetric practice. Implementation of standard labour management strategies can reduce primary caesarean section rate without compromising maternal and fetal safety. One important strategy is ROBSON ‘S 10 GROUP classification system for caesarean section needs to be adopted. Targets of care needs to be set up which also depends on the available resources and expertise. With continuous critical review as described and frequent comparison with other delivery units, the caesarean section rate in each individual unit can be reduced to an appropriate level.